Brain dynamics associated with navigation in 3-D space - Gramann, Klaus; Riecke, B. E.; Wing, Shawn; Jung, Tzyy-Ping; Viirre, Erik (Neuroscience 40th Annual Meeting, 2010)
Spatial navigation is a complex task that requires integration of multisensory information on the navigator's movement in space based on distinct reference frames (e.g., egocentric or allocentric reference frames). Even though different reference frames contribute to successful spatial orienting, several factors influence the use of one or the other system. One factor is an individual proclivity to use distinct reference frames during spatial orienting [1-4]. Most studies on spatial navigation investigated spatial orienting in 2-D space demonstrating that visual flow information on heading changes is sufficient to update one's position and orientation. In contrast, updating yaw and pitch rotation based on visual flow seems to be severely limited [5]. However, no study hitherto investigated the influence of individual proclivities in using distinct reference frames during orienting in three-dimensional virtual environments. Here, we investigated homing performances of subjects preferentially using an egocentric or an allocentric reference frame during passages through three-dimensional space with heading changes in yaw and pitch. The subject's task was to keep up orientation during passages through star fields with heading changes in the horizontal or the vertical plane, unpredictable on a trial. At the end of a passage subjects had to adjust a homing arrow so as to point back to the origin of their passage. The angle of heading changes in yaw and pitch were systematically varied, with angles of 25, 50, 75, or 90deg (up/down, left/right). High density EEG was recorded continuously and analyzed using Independent Component Analysis (ICA) and subsequent clustering of independent components (ICs). Subjects preferentially using an egocentric or an allocentric reference frame revealed comparable homing accuracy for heading changes in pitch and yaw. Importantly, approximately half of the subject with a proclivity for an egocentric reference frame used the preferred frame for horizontal heading changes only but switched to an allocentric reference frame for heading changes in the pitch plane. The brain dynamics underlying spatial orienting for horizontal heading changes replicated previous results with increased activity in a wide spread cortical network during the passage [6]. Heading changes in pitch were associated with increased activity within a comparable network with differences in task-related spectral perturbations as compared to heading changes in yaw. We will discuss common patterns and differences in bran dynamics associated with the use of distinct reference frames for heading changes in pitch and yaw. 1 Gramann, K., El Sharkawy, J., & Deubel, H., Eye-movements during navigation in a virtual tunnel. Int J Neurosci 119 (10), 1755-1778 (2009). 2 Gramann, K., Muller, H.J., Eick, E.M., & Schonebeck, B., Evidence of separable spatial representations in a virtual navigation task. J Exp Psychol Hum Percept Perform 31 (6), 1199-1223 (2005). 3 Riecke, B.E., Consistent left-right reversals for visual path integration in virtual reality: More than a failure to update ones heading? Presence-Teleop Virt 17 (2), 143-175 (2008). 4 Iaria, G., Petrides, M., Dagher, A., Pike, B., & Bohbot, V.D., Cognitive strategies dependent on the hippocampus and caudate nucleus in human navigation: variability and change with practice. J Neurosci 23 (13), 5945-5952 (2003). 5 Vidal, M., Amorim, M.A., & Berthoz, A., Navigating in a virtual three-dimensional maze: how do egocentric and allocentric reference frames interact? Cognitive Brain Research 19 (3), 244-258 (2004). 6 Gramann, K. et al., Human Brain Dynamics Accompanying Use of Egocentric and Allocentric Reference Frames during Navigation. J Cogn Neurosci (2009).
Keywords: Riecke; Riecke_2010; bernhard-riecke; conferenceTalksWithoutPaper; iSpaceWeb; klaus-gramann; point-to-origin; proj--Gramann-PathInt; talkWithoutPaper